THE CORRELATION OF BETWEEN BREAST CANCER KNOWLEDGE LEVELS AND BREAST SELF-EXAMINATION BEHAVIOR (BSE) IN CLASS X AND X1 TEENAGE GIRLS AT GLOBAL ISLAMIC HIGH SCHOOL TERATAI PUTIH BEKASI IN 2022 - Maudy Damayanti; Nurti Y.K. Gea; Meliyana, Ernauli (Rena Cipta Mandiri, 2023)
Background: According to data from Global Burden Cancer in the International Agency for Research On Cancer (IARC), it is known that breast cancer is a disease with the highest percentage of new cases (after controlling for age), which is 43.3%, and the percentage of deaths (after being controlled by age ) due to breast cancer by 12.9% (Kendal, 2022). Breast cancer (carcinoma mammae) itself is a condition where cells have lost their normal control and mechanism, resulting in abnormal, fast, and uncontrolled growth that occurs in breast tissue (MOH, 2015). However, over time, this disease begins to lead to a younger age, so teenagers (13-20 years) also need to do BSE regularly as an effort to prevent and early detection to reduce the possibility of other diseases caused by these risks factors (WHO, 2007). Objectives: This study aims to determine the correlation of between knowledge levels of breast cancer and breast self-examination behavior (BSE) in class X and XI adolescent girls at Teratai Putih Global Islamic High School Bekasi in 2022. Methods: The research method that will be carried out by researchers is quantitative. The design in this study uses Analytical Observation with a Cross-Sectional research design. The population in this study was 66 young women in classes X and XI at the global white lotus Islamic high school. The sampling technique used in this research is total sampling. Results: it was found that with a significant level of 95% or a value of 5% (0.05) the results of the Fisher's Exact Test obtained a p-value (0.00) < value of (0.05) there was a Correlation between the level of knowledge of breast cancer with examination behavior Breast Self (BSE) for Teenage Girls in Class X and XI at Teratai Putih Global Islamic High School Bekasi in 2022. Conclusion: There is a correlation between the level of knowledge of breast cancer and the behavior of breast self-examination (BSE) in Class X and XI Teenage Girls at Teratai Putih Global Islamic High School Bekasi 2022.